Two-scale micromechanical modeling of the time dependent relaxation modulus of plain weave polymer matrix composites. (May 2015) - Xu, Yingjie; Zhang, Pan; Zhang, Weihong
Abstract: In this study, a micromechanical model is presented for prediction of the time dependent relaxation modulus of plain weave polymer matrix composites. This model is based upon the analysis of the representative volume element (RVE) of composites. The RVE models are firstly created on two scales consisting of the fiber bundle modeling (fiber-scale) followed by a weave fabric modeling (bundle-scale). The material properties of fiber and matrix are described by linear elastic law and viscoelastic constitutive law respectively. The generalized Maxwell rheological model is used to describe the viscoelastic behavior of matrix. A time dependent strain energy model is then proposed for evaluating the relaxation modulus of composites. Stress relaxation experiments are conducted for plain weave T300 carbon fabric reinforced 5105 AXSON epoxy resin composites with different fiber volume fractions. Predictions are compared with experimentally measured response to verify the proposed model. In addition, a series of numerical simulations are performed to examine the influences of the loading time and fiber volume fraction on the relaxation behavior of composites.